Rhamnose-induced propanediol oxidoreductase in Escherichia coli: purification, properties, and comparison with the fucose-induced enzyme. - Boronat, A (1979)
Escherichia coli are capable of growing anaerobically on L-rhamnose as a sole source of carbon and energy and without any exogenous hydrogen acceptor. When grown under such condition, synthesis of a nicotinamide adenine dinucleotide-linked L-lactaldehydepropanediol oxidoreductase is induced. The functioning of this enzyme results in the regeneration of nicotinamide adenine dinucleotide. The enzyme was purified to electrophoretic homogeneity. It has a molecular weight of 76,000, with two subunits that are indistinguishable by electrophoretic mobility. The enzyme reduces L-lactaldehyde to L-1,2-propanediol with reduced nicotinamide adenine dinucleotide as a cofactor. The Km were 0.035 mM L-lactaldehyde and 1.25 mM L-1,2-propanediol, at pH 7.0 and 9.5, respectively. The enzyme acts only on the L-isomers. Strong substrate inhibition was observed with L-1,2-propanediol (above 25 mM) in the dehydrogenase reaction. The enzyme has a pH optimum of 6.5 for the reduction of L-lactaldehyde and of 9.5 for the dehydrogenation of L-1,2-propanediol. The enzyme is, according to the parameters presented in this report, indistinguishable from the propanediol oxidoreductase induced by anaerobic growth on fucose.